THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY ON CORPORATE IMAGE AND CORPORATE REPUTATION AND IMPLICATIONS FOR PURCHASE INTENTION (Studies in Samarinda AQUA customers) - Dinata, Andi Irma; Achmad, Gusti Noorlitaria; ZA, Saida Zainurossalamia (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The purpose of this study was to determine the effect of CSR on corporate image, corporate reputation, and purchase intention. The unit of analysis in this study is the customer AQUA of product in Samarinda. The sample in this study was 120 respondents with accidental sampling with a sampling approach. Data were collected using a questionnaire distributed to respondents, and then analyzed using a questionnaire scale Linkert 5 and using product Static analysis tools and Service Solutions (SPSS) version 17 and Structural Equation Modeling (SEM) AMOS Version 22. The analysis shows that CSR has a significant influence of the company's image, reputation of the company, and does not have a strong influence on purchase intention. Based on the results of data analysis found that the company's image and reputation of the company has a significant impact on purchase intention.